LOST SPACE IN URBAN CORE AREAS OF KUALA LUMPUR IN RELATIONS TO PHYSICAL URBAN ENVIRONMENT - Khalid, Nurul Shakila; Hilal, Sabirah; Nasrudin, Na’asah; Marzukhi, Marlyana Azyyati (PLANNING MALAYSIA, 2018)
The process of urban development today treats buildings as isolated objects, not as part of the larger fabric of streets, squares, parks and viable open space, and without an understanding of human behaviour. What emerges in most environmental settings is unshaped antispace. The essence of this research seeks to establish a better understanding towards the local perception of lost space in the urban core areas of Kuala Lumpur and identify the appropriate tools to improve the usability of the space. The research has been designed with the aim of seeking effective ways of designing a space in the urban core to minimize the undermanaged space. For this reason, the research focuses on the definitions and characteristics of lost space before the process of designing the space. A qualitative analysis is made on selected parameters in the theory of lost space by Trancik (1986); activities, accessibility, connectivity, maintenance and design aspect. Through a qualitative approach, the result indicates that there were various new perceptions of descriptive lost space includes economic and social activity, connectivity, and accessibility as these are an important strategy for maintaining the vitality and robustness of urban space. It is proposed in this paper that more attention should be given to urban areas to continue to give cities’ life and vitality, and the most significant result is to achieve holistic sustainable planning and management of urban space.